STUDIES ON THE EXCHANGE OF VALINE-OXYGEN DURING THE BIOSYNTHESIS OF DELTA-(L-ALPHA-AMINOADIPOYL)-L-CYSTEINYL-D-VALINE - Baldwin, J; Adlington, R; Bird, J; Field, R; Ocallaghan, N; Schofield, C (1992)
Incorporation of [4-2H6,18O2]-valine into δ-(L)-α-aminoadipoyl)-L-cysteinyl-D-valine (ACV), by intact cells of Cephalosporium acremonium, demonstrated the intracellular exchange of one and both valine oxygen atoms. Incubation of [18O2]-valine with the purified ACV synthetase from C. acremonium gave exclusive incorporation of a single 18O label into ACV, consistent witheffectively non-reversible formation of a covalent valinoyl-ACV synthetase intermediate under in vitro conditions. © 1992.